O Sistema Internacional de Proteção dos Direitos da Criança Refugiada: uma análise sobre a utilização da detenção administrativa de crianças refugiadas nos estados para efeitos de controle migratório - Cruz Filho, Marco Antonio Lima da (2024)
With the increase in migratory flows and the tightening of migration policies in Europe and the United States, the issue of the administrative detention of refugee children has become a pressing concern. This is due to its frequent use as a measure to control borders and residency within a territory. However, national practices in this area clash with the robust international legal framework of human rights, children's rights, and international refugee law. Therefore, this research highlights the inherent incompatibility of detention with the best interests of the child principle, detailing the resulting human rights violations and proposing, based on international guidelines and practical examples, more effective and humane protection alternatives